Diversidade genética e sistema de reprodução de jaboticabeiras nativas e plantadas - Gil, Bruna Valeria (2023)
Knowing the status of genetic diversity is the first step to determining strategies for conservation, domestication, and use of genetic resources of perennial fruit species. For this reason, characterizing the reproductive system is important to assist in designing strategies for using and conserving species with relevant regional importance. The jaboticabeira (Plinia spp.) is a native species of Brazil and is subject to habitat fragmentation, mainly due to human activity, and therefore requires conservation strategies. This work aimed to estimate the genetic diversity in jaboticaba tree populations in natural and planted areas and investigate the species reproduction system. For this, two experiments were carried out: (a) analysis of the genetic structure and diversity of 20 populations of jaboticaba trees from four Brazilian states (RS, SC, PR, and MG), 14 natural and six planted populations; (b) detection of the reproduction system of the species, based on progenies derived from seeds of 13 mother jaboticaba trees. These leaf samples were collected to be genotyped with 13 microsatellite molecular markers. The results indicate that the jaboticaba populations present exclusive alleles in a few populations, alleles with high frequency in most populations, and low genetic divergence among populations. The 20 populations analyzed can be divided into only two main groups by the similarity cluster analyses, the first composed of natural populations, except the population of Imbituva, and the second with planted collections. The planted collections showed higher genetic diversity than the natural ones and are important sources of genetic variability for conservation and use. The population genetic structure was unrelated to their distribution or geographical distance. The jaboticaba tree has a mixed reproduction system, with a predominance of selfing in progenies from seeds. Most crosses occur between unrelated individuals, and seedlings from these fruits predominantly reach the adult stage. For the formation of new active germplasm collections, it is suggested to select genotypes with characteristics of interest, which may come from a few populations, but preferably those with greater genetic diversity and carriers of unique alleles.